1970
DOI: 10.1113/expphysiol.1970.sp002056
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Lymphatic Vessels of the Bat's Wing

Abstract: The lymphatics of the bat's wing could be separated in vivo into two morphologically and functionally distinct types. Vessels selected for subsequent electron microscopy were labelled in vivo with Berlin blue which could be readily identified in the electron microscope. The terminal bulbs which are responsible for absorption of fluid and particles from the tissues have walls composed of a single layer of endothelium lined on its abluminal surface by a generally tenuous condensation of fibrillar material. Absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In this study we have observed some aspects of the microanatomy and ultrastructure of the ThD and its march valves that have been previously reported (Albertine et al 1982;B6rst et al 1969;Casley-Smith 1969;Cliff andNicoll 1970, Daroczy 1984;Gnepp 1976;Gnepp andGreen 1979, 1980;Lauweryns and Boussauw 1973;Marais and Fossum 1988;Schipp 1968;Takada 1971;Vajda and Tomcsik 1971). Our own observations have allowed us to systematize and review the previous data in the light of modern liquidodynamics in vessels and the functions of the cytoskeleton.…”
Section: Discussionmentioning
confidence: 58%
“…In this study we have observed some aspects of the microanatomy and ultrastructure of the ThD and its march valves that have been previously reported (Albertine et al 1982;B6rst et al 1969;Casley-Smith 1969;Cliff andNicoll 1970, Daroczy 1984;Gnepp 1976;Gnepp andGreen 1979, 1980;Lauweryns and Boussauw 1973;Marais and Fossum 1988;Schipp 1968;Takada 1971;Vajda and Tomcsik 1971). Our own observations have allowed us to systematize and review the previous data in the light of modern liquidodynamics in vessels and the functions of the cytoskeleton.…”
Section: Discussionmentioning
confidence: 58%
“…Part of the explanation for the difference in response may be in the innerva tion of the mesenteric lymphatics [Vajda, 1966;Alessandrini et al, 1981;Ohhashi et al, 1982] and the apparent absence of inner vation of the lymphatics in the bat's wing [Fleming and McKinney, 1985], The con tractile elements of the mesenteric lymphat ics may also be different from the initial lym phatics. Initial lymphatics of the wing of Miniopterus schreibersi, an Australian bat, consist of only a single layer of endothelial cells [Cliff and Nicoll, 1970]. Nicoll [1975] believed that typical vascular cells were also lacking in the spontaneously contractile ini tial lymphatics of the wing of the little brown bat, Myotis lucifugus.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that venular and lymphatic contractions are both initiated by a common neural, electrical, or humoral factor must be addressed. First, venules and lymphatic microvessels in bats are not innervated (6,28,54). If a venule and an adjacent lymphatic microvessel were jointly innervated in the bat wing, there would have to be a consistent delay before the initiation of lymphatic contraction.…”
Section: Discussionmentioning
confidence: 99%